2009
DOI: 10.1111/j.1540-6040.2009.01288.x
|View full text |Cite
|
Sign up to set email alerts
|

The Missing Organizational Dimension in Urban Sociology

Abstract: Our article takes issue with the treatment of organizations in much urban sociology. We argue that both Marxian political economists and Chicagoan ethnographers and quantitative analysts treat organizations as derivative rather than productive of urban social relations. This problem is not epistemological or methodological. Instead, it is rooted in the objects of analysis that urban sociologists choose. Drawing on key elements of structuration theory, we attempt to lay the groundwork for improving the treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
120
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(129 citation statements)
references
References 110 publications
(170 reference statements)
7
120
0
2
Order By: Relevance
“…Although growth-machine politics and the influence of wealthy corporations continue to influence economic development, episodes such as the collapse of the multibillion dollar plan for the 2024 Boston Olympics in the face of widespread public opposition-in considerable part over environmental concernsreveal the increasing importance of civic engagement and grassroots opposition in the politics of urban planning. In addition, the devolution of federal resources in the last few decades has resulted in a sharp move away from direct transfers (e.g., welfare payments to individuals) toward nonprofit organizations serving as mediators of federal support to low-income populations (27,28), reshaping the form of local urban governance. New research in Boston, for example, has also found that community-based organizations superseded elected politicians as the legitimate representatives of the city's economic and infrastructure development of a large corridor running through poor minority neighborhoods (29).…”
Section: Social Mechanisms and Processes Underlying Sustainabilitymentioning
confidence: 99%
“…Although growth-machine politics and the influence of wealthy corporations continue to influence economic development, episodes such as the collapse of the multibillion dollar plan for the 2024 Boston Olympics in the face of widespread public opposition-in considerable part over environmental concernsreveal the increasing importance of civic engagement and grassroots opposition in the politics of urban planning. In addition, the devolution of federal resources in the last few decades has resulted in a sharp move away from direct transfers (e.g., welfare payments to individuals) toward nonprofit organizations serving as mediators of federal support to low-income populations (27,28), reshaping the form of local urban governance. New research in Boston, for example, has also found that community-based organizations superseded elected politicians as the legitimate representatives of the city's economic and infrastructure development of a large corridor running through poor minority neighborhoods (29).…”
Section: Social Mechanisms and Processes Underlying Sustainabilitymentioning
confidence: 99%
“…For example, McQuarrie and Marwell (2009) argued for an examination of organizations not as products of urban social processes but agents that produce urban social processes. In particular, they advocated the use of institutional and organizational perspectives to explain how organizations structure the lives of residents, mediate neighborhood change, and facilitate or constrain neighborhood resources.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, social scientists have argued for a shift in thinking about the role organizations play in neighborhoods (McQuarrie & Marwell, 2009;Small, 2009). For example, McQuarrie and Marwell (2009) argued for an examination of organizations not as products of urban social processes but agents that produce urban social processes.…”
Section: Discussionmentioning
confidence: 99%
“…For Foucault (1977, p. 10), the apparatus is a "heterogeneous grouping composing discourses, institutions, architectural arrangements, policy decisions, laws, administrative measures, scientific statements, philosophic, moral and philanthropic propositions." 2 As a relational entity that links these various components, a governing apparatus effects a "disciplinary normalization" on urban space not merely by codifying norms as laws, but also through spatial practices (see also e.g., Lefebvre 1976;Merry 2001) and the "mediating" functions that are the focus of McQuarrie and Marwell's (2009) organizational sociology. Inherent to both of these approaches is the perspective that power is productive.…”
Section: Organizations and Governmentalitymentioning
confidence: 99%
“…The perspective draws from structuration theory (Giddens 1991), focusing on the flexible, relational functioning of organizations, both among each other (in the network) and as "meso level" mediators (McQuarrie and Marwell 2009). Also relevant to understanding the role of neighborhood organizations in the governing arrangements of gentrification are the insights of the notion of "governmentality" (Foucault 1979a;Foucault et al 1991), which "refers to the rationalities and mentalities of governance as well as the range of tactics and strategies that produce social order"…”
Section: Organizations and Governmentalitymentioning
confidence: 99%